2016
DOI: 10.1088/1054-660x/26/2/025103
|View full text |Cite
|
Sign up to set email alerts
|

Erbium-doped fiber triple-ring laser configuration with single-longitudinal-mode dual-wavelength output

Abstract: In this investigation, we propose and demonstrate a stabilized single-longitudinal-mode (SLM) dual-wavelength erbium-doped fiber (EDF) laser triple-ring cavity. Here, two fiber Bragg gratings (FBGs) are used inside the fiber cavity to generate dual-wavelength output. In order to complete the SLM output, the triple-ring configuration is utilized for suppressing the densely multi-longitudinal mode (MLM). The output powers and wavelengths of  −8.4 and  −8.5 dBm and 1535.76 and 1543.28 nm are obtained in the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As a result, various approaches have been reported to achieve multi-wavelength oscillation in EDF lasers. Most of these ring fiber laser cavities are based on all-fiber structures such as arrayed waveguide gratings [7], fiber Bragg gratings (FBGs) [8][9][10], Mach-Zehnder interferometers (MZI) [11,12], Fabry-Perot interferometers [13,14], nonlinear fibers [15], tapered fibers [16] and Sagnac interferometers [17,18]. Yeh et al demonstrated a stabilized single-longitudinal-mode (SLM) dual-wavelength EDF laser triple-ring cavity [8].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, various approaches have been reported to achieve multi-wavelength oscillation in EDF lasers. Most of these ring fiber laser cavities are based on all-fiber structures such as arrayed waveguide gratings [7], fiber Bragg gratings (FBGs) [8][9][10], Mach-Zehnder interferometers (MZI) [11,12], Fabry-Perot interferometers [13,14], nonlinear fibers [15], tapered fibers [16] and Sagnac interferometers [17,18]. Yeh et al demonstrated a stabilized single-longitudinal-mode (SLM) dual-wavelength EDF laser triple-ring cavity [8].…”
Section: Introductionmentioning
confidence: 99%